Maternal High-Fat Diet Exposure During Gestation and Lactation Affects Intestinal Development in Suckling Rats - Słupecka-Ziemilska, Monika; Grzesiak, Paulina; Kowalczyk, Paweł; Wychowański, Piotr; Woliński, Jarosław (Frontiers in Physiology, 2021)
Maternal health and diet influence metabolic status and play a crucial role in the development of metabolic function in offspring and their susceptibility to metabolic diseases in adulthood. The pathogenesis of various metabolic disorders is often associated with impairment in intestinal structure and function. Thus, the aim of the current study was to determine the effects of maternal exposure to a high fat diet (HFD), during gestation and lactation, on small intestinal growth and maturation in rat pups at 21 days old. Female, Wistar Han rats were fed either a breeding diet (BD) or high fat diet (HFD), from mating until the 21st day of lactation. Maternal HFD exposure increased body weight, BMI and adiposity. Compared to the maternal BD, HFD exposure influenced small intestine histomorphometry in a segment-dependent manner, changed the activity of brush border enzymes, and had an impact on intestinal contractility via changes in cholinergic signaling. Moreover, offspring from the maternal HFD group had upregulated mRNA expression of cyclooxygenase (COX)-2, which plays a role in the inflammatory process. These results suggest that maternal HFD exposure, during gestation and lactation, programs the intestinal development of the offspring in a direction towards obesity as observed changes are also commonly reported in models of diet-induced obesity. The results also highlight the importance of maternal diet preferences in the process of developmental programming of metabolic diseases.